PERSEPSI DAN MINAT MASYARAKAT KOTA BEKASI TERHADAP MADRASAH: STUDI KUALITATIF ORANG TUA MURID MAN 2 KOTA BEKASI - Rabiyannur Lubis (Turats, 2020)
This study describes the perception and interest of the people of the city of Bekasi towardsmadrasas: a qualitative study of parents at MAN 2 Bekasi. The results of the study explained that thecommunity had a high interest and enthusiasm in sending their children to school at MAN 2 Bekasi City.This is motivated by the fact that madrasas provide religious knowledge and receive moral educationfor the lives of their children now and in the future. In its curriculum, MAN 2 Bekasi City gives a lotof weight in the subjects of religious sciences, such as Akidah, Morals, Tafsir, Hadith, Jurisprudence,Kalam, and Arabic. In addition, several factors are supporting and inhibiting public perception ofmadrasas. The supporting factors are, madrasas can develop religious values and noble character;Madrasas are considered to provide learning in the affective aspect, namely the development ofchildren’s behavior or morals, the number of extracurricular activities that are religious in nature,supporting infrastructure, and the performance of teachers who consistently guide students’ religiousactivities. The inhibiting factors for public perception of madrasas, among others, are the low-qualityimage of madrasas compared to general schools, low professionalism caused by low mental attitudes,not yet growing quality culture, and external factors in the form of negative effects of electronic media,especially the internet.